Crypt4GH-JS: securely storing sensitive data online with client-side encryption - Thelen, Fabienne; Hochmuth, Jannis; Griep, Sven; Schwab, Benedikt; Goesmann, Alexander; Förster, Frank; Justus Liebig University Giessen (My University, 2025)
Motivation and Results: Crypt4GH-JS is a browser-ready implementation of the Crypt4GH file encryption standard written in JavaScript. While having minimal to no impact on data upload and download throughput this library enables on-the-fly encryption of arbitrary data in web applications, regardless of whether on the client or server side. As development moves more and more toward cloud-native applications, this library represents a significant step forward for flexible data security in the context of opaque cloud storage systems. Availability and implementation: Crypt4GH-JS can be installed via Node Package Manager (https://www.npmjs.com/package/crypt4gh_js) or through its public GitHub Repository (https://github.com/fathelen/crypt4ghJS), where the source code is available. Crypt4GH-JS can be tested in the browser using our demonstration website, which can be found at: https://fathelen.github.io/crypt4ghJS/.
Keywords: ddc:570